Proton pump inhibitor use and risk of hip fractures among community‐dwelling persons with Alzheimer's disease—a nested case‐control study. Issue 8 (6th March 2018) - Torvinen‐Kiiskinen, S.; Tolppanen, A.‐M.; Koponen, M.; Tanskanen, A.; Tiihonen, J.; Hartikainen, S.; Taipale, H.
Summary: Background: Hip fractures are a major health concern among older persons with Alzheimer's disease, who usually use many concomitant drugs for several diseases. Evidence of the association between proton pump inhibitor use and risk of hip fracture is contradictory. Aim: To investigate whether the long‐term use of proton pump inhibitor is associated with risk of hip fractures among community‐dwelling persons with Alzheimer's disease. Methods: In this nested case‐control study, the nationwide MEDALZ data were utilised. Community‐dwelling persons with Alzheimer's disease who encountered incident hip fracture (N = 4818; mean age 84.1) were included as cases. Four controls were matched for each case at the date of hip fracture (N = 19 235; mean age 84.0). The association between hip fracture and duration of current PPI use (ongoing use during 0‐30 days before the index date), and cumulative duration of use during 10 years before was investigated with conditional logistic regression. Results: Long‐term or cumulative proton pump inhibitor use was not associated with an increased risk of hip fracture. Current proton pump inhibitor use was associated with an increased risk of hip fracture (adjusted OR 1.12, 95% CI 1.03‐1.22). The risk was increased in short‐term current use (<1 year) (adjusted OR 1.23, 95% CI 1.10‐1.37). Conclusions: The increased risk of hip fracture was evident only in short‐term proton pump inhibitor use, but no association was found for long‐term or cumulative use. Thus, our findings do not support previous assumptions that long‐term proton pump inhibitor use would be associated with an increased risk of hip fractures. Abstract : Linked Content This article is linked to Targownik, Torvinen‐Kiiskinen et al, Sugiyama and Zhao et al papers. To view these articles visit https://doi.org/10.1111/apt.14640, https://doi.org/10.1111/apt.14666, https://doi.org/10.1111/apt.14641 and https://doi.org/10.1111/apt.14661 .